Improved Methods for Single‐Molecule Fluorescence In Situ Hybridization and Immunofluorescence in Caenorhabditis elegans Embryos. Issue 11 (26th November 2021) - Parker, Dylan M.; Winkenbach, Lindsay P.; Parker, Annemarie; Boyson, Sam; Nishimura, Erin Osborne
Abstract: Visualization of gene products in Caenorhabditis elegans has provided insights into the molecular and biological functions of many novel genes in their native contexts. Single‐molecule fluorescence in situ hybridization (smFISH) and immunofluorescence (IF) enable the visualization of the abundance and localization of mRNAs and proteins, respectively, allowing researchers to ultimately elucidate the localization, dynamics, and functions of the corresponding genes. Whereas both smFISH and immunofluorescence have been foundational techniques in molecular biology, each protocol poses challenges for use in the C. elegans embryo. smFISH protocols suffer from high initial costs and can photobleach rapidly, and immunofluorescence requires technically challenging permeabilization steps and slide preparation. Most importantly, published smFISH and IF protocols have predominantly been mutually exclusive, preventing the exploration of relationships between an mRNA and a relevant protein in the same sample. Here, we describe protocols to perform immunofluorescence and smFISH in C. elegans embryos either in sequence or simultaneously. We also outline the steps to perform smFISH or immunofluorescence alone, including several improvements and optimizations to existing approaches. These protocols feature improved fixation and permeabilization steps to preserve cellular morphology while maintaining probe and antibody accessibility in the embryo, a streamlined, in‐tube approach for antibody staining that negates freeze‐cracking, a validated method to perform the cost‐reducing single molecule inexpensive FISH (smiFISH) adaptation, slide preparation using empirically determined optimal antifade products, and straightforward quantification and data analysis methods. Finally, we discuss tricks and tips to help the reader optimize and troubleshoot individual steps in each protocol. Together, these protocols simplify existing workflows for single‐molecule RNA and protein detection. Moreover, simultaneous, high‐resolution imaging of proteins and RNAs of interest will permit analysis, quantification, and comparison of protein and RNA distributions, furthering our understanding of the relationship between RNAs and their protein products or cellular markers in early development. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Sequential immunofluorescence and single‐molecule fluorescence in situ hybridization Alternate Protocol : Abbreviated protocol for simultaneous immunofluorescence and single‐molecule fluorescence in situ hybridization Basic Protocol 2 : Simplified immunofluorescence in C. elegans embryos Basic Protocol 3 : Single‐molecule fluorescence in situ hybridization or single‐molecule inexpensive fluorescence in situ hybridization